A Review of Public Secondary Schools Effectiveness in Nigeria: Challenges and Managing Strategies - S.I. , Bashar; M.A. , Yasin (International Journal of Psychosocial Rehabilitation, 2020)
The global trends of education in the developed nations shift towards the direction of the fourth and fifth industrial revolutions, which are characterized by advances in science and technology that led to the emergence of robotics, the Internet of Things, artificial intelligence, bio- and nanotechnologies, autonomous vehicles, quantum computing, material science, and energy storage in global societies. This is a great challenge to the third-world countries-—Nigeria inclusive—that are still striving to see themselves through the 2nd and 3rd industrial revolutions in their education sectors. However, this could never be achieved until schools at all levels become smart, successful, and effective. Although literature indicated that public secondary schools in Nigeria were not performing effectively, however, there was hardly any article that compiled all the major factors responsible for this ineffective performance of the schools. The purpose of this paper, therefore, is to review and compile the challenges that compromise the effectiveness of the schools and suggest their possible managing strategies. To achieve this, articles were reviewed using appropriate methods as well as inclusion and exclusion criteria. It was found from the review that public secondary schools in Nigeria suffer from substandard leadership, infrastructural decay, overcrowded classrooms, and lots more. To manage these situations, this paper recommends that qualified principals and teachers be provided for the schools, intensive training be provided for both the principals and teachers, more classroom structures be built, and security measures be provided in the schools.